Problems in the Development and Management Of Projects Related To The Creation Of Renewable Energy Resources (Texas Journal of Multidisciplinary Studies, 2022)
The article examines the opinions of the world's leading scientists on the problems in the development and management of projects related to the creation of renewable energy resources, summarizes the forecasts of global renewable energy consumption until 2040, the economic impact of the increase in the use of renewable energy sources in some countries of the world(forecasts for 2020-2030) were studied, justified conclusions and proposals were developed on the problems in the development and management of projects related to the creation of renewable energy resources, and recommendations were given for their application in our country.